Metafora pojęciowa w interpretacji teorii osobistych – analiza krytyczna - Strugielska, Ariadna; Strzemeski, Krzysztof (Neofilolog, 2010)
In this pilot study, a group of students were asked to generate metaphors on the role of the teacher and the learner and learning and teaching. Then the questionnaire data were compared with student metaphors elicited in oral interviews. The results suggest that sentence completion does not reflect informants’ true convictions, and that in contrast to theoretical assumptions, novel metaphors seem to be more consistent than conventional metaphors.